Upaya Peningkatan Pencapaian Service Level Agreement Penyusunan Opini Risiko Pembiayaan di Bank Mandiri - , INDRIA PURWANINGSIH ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The purpose of this study is to investigate the application of operation management at the Risk Management Division of Bank Syariah Mandiri in an effort to improve the achievement of targeted service level agreement (SLA) in making financing risk opinion / RO, to identify the causes of low achievement on targeted SLA, and to formulate solutions to solve the problem. Some factors leading to the unfulfillmentment of SLA target, among others, is the high volume of proposals coming into RO constituent units, the bottleneck at the level of section chief and deputy division head, limited accessibility on supporting data, high complexity of corporate financing, high frequency of rework/revision, and less compact RO. Squeezing activity can reduce the consumption of time required in producing RO. Squeezing activity is done by making changes on the input, process and output. Changes in input are by reducing the volume of financing proposals that require RO by increasing financing limit of the branch offices, providing a comprehensive data bank, and establishment of risk acceptance criteria (RAC). Changes in process are by providing scoring / rating system to substitute RO, placement of RO provider unit representative at region offices or at particular branch offices, and providing RO checklist. A change in output is by simplifying RO presentation format. Higher complexity and more stages in making RO for corporate financing has caused longer time consumption in making corporate financing RO than noncorporate financing RO. Therefore, the SLA for corporate financing RO shall be changed from 2 days to 3 days for division head level, and 4 days for director level.